Chronique juridique - Moreau, Rémi (Assurances, 1981)
A discharge is always a very serious matter for an employee and Canadian courts have handed down numerous rulings respecting unjustified discharges. In his article, Me Rémi Moreau presents and comments upon several of such rulings. In each instance, the court has awarded indemnities which vary in accordance with the facts and circumstances of the individual cases.